Scalable metamaterial antenna arrays with suppressed mutual coupling for compact platforms - Wilcher, Alexander; David Cerpa, Ariel; Yoon, Yong-Kyu (Frontiers in Antennas and Propagation, 2025)
This study presents metamaterial arrays featuring point-symmetric, dimensionally optimized meander-line (ML) complementary split ring resonators (CSRRs) to reduce mutual coupling between closely spaced microstrip patch antennas (MPAs) at a center frequency of 5.8 GHz. The compact nature of these array elements enables reduced form factors for size, weight, and power (SWaP)-constrained applications. This approach is expected to provide improved signal-to-noise ratio and electronic beam steering by accommodating more elements within a fixed area than traditional arrays. Simulations conducted using the Advanced Design System (ADS, Keysight Inc.) assessed the feeding structures for arrays of 4, 16, and 64 elements, while the High-Frequency Structure Simulator (HFSS, ANSYS Inc.) was used to optimize and simulate both the feeding structures and complete arrays to evaluate scalability. The 4-element MMA unit cell has a spacing of 3 mm, which is approximately a 16th (∼λ/16) of the free space wavelength (λ), while reference MPA arrays use a conventional spacing of 25.8 mm (∼λ/2). A comparison reveals that the reduced surface area in MMAs impacts beam patterns and realized gain. Simulations indicate that as the number of elements increases, area reduction reaches nearly 80% for the ideal simulated 64-element case. MMAs offer polarization reconfiguration and adjustable element spacing, giving design flexibility while retaining significant area advantages. To validate the simulations, 2 × 2 and 4 × 4 reference and MMAs were fabricated and characterized. The 8 × 8 designs were not fabricated due to excessive FR4 substrate losses and the complexity of compact feeding structures. Arrays were manufactured by Sunstone Circuits using standard printed circuit board processes, ensuring the simple, accurate, and low-cost fabrication of designs. Characterization by the University of Florida and Rohde and Schwarz confirmed that measurement results closely match simulations, showing MMA size reductions of 76.83% and 77.02% compared to reference arrays, with realized gains of 6.22 dB and 9.38 dB for the 4- and 16-element MMAs, respectively. These MMA architectures are expected to benefit compact wireless RF systems in both the defense and commercial sectors, including radar and communication applications.